2010
DOI: 10.1074/jbc.m109.055525
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 Modulates DNA Damage-mediated Phosphorylation of Tumor Suppressor p53 at Ser-15 and Acts as a Co-activator for p53

Abstract: Although it has been shown that the gastric tumor suppressor RUNX3 has a growth inhibitory activity, the precise molecular mechanisms behind RUNX3-mediated tumor suppression remained unclear. In this study, we found that RUNX3 is closely involved in DNA damage-dependent phosphorylation of tumor suppressor p53 at Ser-15 and acts as a co-activator for p53. The small interference RNA-mediated knockdown of RUNX3 inhibited adriamycin (ADR)-dependent apoptosis in p53-proficient cells but not in p53-deficient cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…Although the molecular mechanisms underlying the pro-apoptotic effects of TGF␤ appear to be cell type-dependent, it is likely that RUNX family members such as RUNX1 and RUNX3 are the key components during this cellular process. Recently, we have found that RUNX3 participates in p53-dependent DNA damage response (56). Based on our results, RUNX3 was induced to access the cell nucleus following DNA damage and formed a complex with p53 to enhance its transcriptional as well as pro-apoptotic activity.…”
Section: Discussionmentioning
confidence: 92%
“…Although the molecular mechanisms underlying the pro-apoptotic effects of TGF␤ appear to be cell type-dependent, it is likely that RUNX family members such as RUNX1 and RUNX3 are the key components during this cellular process. Recently, we have found that RUNX3 participates in p53-dependent DNA damage response (56). Based on our results, RUNX3 was induced to access the cell nucleus following DNA damage and formed a complex with p53 to enhance its transcriptional as well as pro-apoptotic activity.…”
Section: Discussionmentioning
confidence: 92%
“…Hypermethylation and loss are common mechanisms of RUNX3 inactivation in pancreatic cancer (Wada et al, 2004;Nomoto et al, 2008). RUNX3 could act as a coactivator for TP53 by regulating its DNA damage-induced phosphorylation (Yamada et al, 2010). Rearrangements of chromosome arm 8p are one of the most common genetic events in breast, pancreatic and many other epithelial carcinomas (Emi et al, 1992;Tirkkonen et al, 1998;Davidson et al, 2000;Loo et al, 2004;Bashyam et al, 2005), suggesting the presence of candidate tumor suppressor genes; ARHGEF10 (8p23) and TUSC3 (8p22) have been proposed as potential 8p tumor suppressor genes (Cooke et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By checking different time-points of DEN induced generation of liver cancer, Michael R. Speicher et al found that chromosomal gains and losses were early observed in week 32 and increased significantly in week 56. Moreover, the loss of distal chromosome 4q, which contained several HCC suppressor genes such as Runx3 [31] and Nr0b2/Shp [32], occurred early and persisted during all tumor stages. Intriguingly, the mutations and activation of Wnt/β-catenin occurred at late stages, but were not involved in tumor initiation in this model.…”
Section: Environmental and Genetic Susceptibilitiesmentioning
confidence: 98%